1997
DOI: 10.1210/endo.138.11.5508
|View full text |Cite
|
Sign up to set email alerts
|

Fas Antigen-Mediated Apoptosis of Ovarian Surface Epithelial Cells*

Abstract: The Fas antigen is a cell surface receptor that, when engaged by Fas ligand or specific agonistic antibodies, triggers apoptosis. The effect of an agonistic monoclonal antibody to mouse Fas antigen (Fas mAb, clone J02) on the viability of cells from dispersed mouse corpora lutea (CL cultures) was tested. Cultures were prepared by enzymatic digestion of CL from day 4 -7 pseudopregnant mice. Cultures were pretreated with 0, 1, 10, 100, or 1000 U/ml murine interferon-␥ (IFN) at 72 h of culture. IFN has been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Like thecal/interstitial cells, ovarian surface epithelial cells do not frequently apoptose. Rather, only those surface epithelial cells associated with the site of follicular rupture at the time of ovulation have been shown to undergo apoptosis at any appreciable rate [26,32]. It is possible that the high levels of PAIRBP1 within these cells could be involved in maintaining their viability because PAIRBP1 mediates P4's antiapoptotic action in granulosa and luteal cells (see subsequent discussion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like thecal/interstitial cells, ovarian surface epithelial cells do not frequently apoptose. Rather, only those surface epithelial cells associated with the site of follicular rupture at the time of ovulation have been shown to undergo apoptosis at any appreciable rate [26,32]. It is possible that the high levels of PAIRBP1 within these cells could be involved in maintaining their viability because PAIRBP1 mediates P4's antiapoptotic action in granulosa and luteal cells (see subsequent discussion).…”
Section: Discussionmentioning
confidence: 99%
“…The only modification was that the cells were stained with YOPRO-1 and Nile Red (5 g/ ml) [25][26][27]. Nile Red stained the lipid droplets, allowing for the identification of well-differentiated luteal cells [25,26].…”
Section: Detection Of Apoptotic Cellsmentioning
confidence: 99%
“…It has been postulated that the first step in tumorigenesis is the formation of epithelial ICs derived from such crypts or by invagination of the surface epithelium [42]. It has been shown that the cells lining these cysts express FasR and are normally removed by apoptosis, and any derangement during this process would allow for persistence of the ICs with increasing risk of developing ovarian cancer [20,43].…”
Section: Discussionmentioning
confidence: 99%
“…Fas antigen mRNA was quantified by a competitive RT-PCR assay described previously for measurement of mouse Fas antigen mRNA [11] and modified for use with bovinespecific primers and controls. RNA was reverse transcribed in the presence of various concentrations of an internal standard RNA.…”
Section: Analysis Of Fas Antigen Mrnamentioning
confidence: 99%
“…Cultured ovarian cells from the human and mouse were resistant to killing by cytotoxic Fas mAb unless the cells were pretreated with the cytokines, interferon (IFN) or IFNϩTNF, or with cycloheximide [3,10,11]. Studies of Fas expression and function in the ovary have been limited pri- 1 This work was supported by grants from the USDA (98-35203-6220) and NIH (HD 32535).…”
Section: Introductionmentioning
confidence: 99%